Estimation Of Run-Up Amplification Factors For Penang - Lim, Yong Hu (2017)
The mega-tsunami that struck Malaysia on 26 December 2004 affected 200 kilometres of northwest Peninsular Malaysian coastline from Perlis to Selangor. This rare catastrophic event has awakened the attention of Malaysian government to take appropriate risk reduction measures, including timely and orderly evacuation. To determine the evacuation zones, the height of the tsunami waves arriving the shore must be predicted. Model simulations are too time-consuming for real time predictions. Therefore, in this thesis, an approach of applying run-up amplification factors to estimate the run-up heights is proposed as a simple way to obtain quick estimation of the run-up heights by multiplying the run-up amplification factors with the offshore incident wave heights detected by tsunami early warning system.